2017
DOI: 10.1016/j.cub.2017.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Warming by 1°C Drives Species and Assemblage Level Responses in Antarctica’s Marine Shallows

Abstract: Forecasting assemblage-level responses to climate change remains one of the greatest challenges in global ecology [1, 2]. Data from the marine realm are limited because they largely come from experiments using limited numbers of species [3], mesocosms whose interior conditions are unnatural [4], and long-term correlation studies based on historical collections [5]. We describe the first ever experiment to warm benthic assemblages to ecologically relevant levels in situ. Heated settlement panels were used to cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(108 citation statements)
references
References 54 publications
2
105
1
Order By: Relevance
“…Advances in macroecology suggest that permanent environmental mosaics, defined by spatial overlaps of non-monotonic environmental gradients ( 7 ), as well as regional adaption or acclimatization ( 810 ), dictate geographic variations in species performance and sensitivity to environmental change in marine ecosystems. Key to these works is that responses vary among populations and individual taxa ( 6 , 8 ), which often play disproportionately strong roles in structuring benthic communities ( 11 ). Thus, species-specific biological mechanisms driving organismal variability may shape differential regional responses of foundation species to co-occurring multiple drivers.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in macroecology suggest that permanent environmental mosaics, defined by spatial overlaps of non-monotonic environmental gradients ( 7 ), as well as regional adaption or acclimatization ( 810 ), dictate geographic variations in species performance and sensitivity to environmental change in marine ecosystems. Key to these works is that responses vary among populations and individual taxa ( 6 , 8 ), which often play disproportionately strong roles in structuring benthic communities ( 11 ). Thus, species-specific biological mechanisms driving organismal variability may shape differential regional responses of foundation species to co-occurring multiple drivers.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that the established Arrhenius relationships in the literature suggest that development and growth rates should increase at a rate of 7-12 % • C −1 of warming (Clarke, 2003), much lower than the observed 74 and 42 % increase in R and GPP respectively per 1 • C of warming in this study. However, recent work in the Antarctic by Ashton et al (2017) on marine benthic assemblages showed that, in some species, the growth rate exhibited a 100 % increase per 1 • C of warming, yielding Q 10 values around 1000. Therefore, while the temperature sensitivity estimates reported in this paper and in Trnovsky et al (2016) exceed the expected rate for biological reactions and enzyme activity, evidence exists in other benthic marine environments to support the notion that the impact of temperature on biochemical processes may be more complex than previously thought at the organism level (Ashton et al, 2017).…”
Section: The Response In Coral Reef Sediment Metabolism To Seawater Wmentioning
confidence: 99%
“…Furthermore, the majority of warming studies on marine sediments have been performed ex situ in more poleward latitudes (temperate to arctic environments) over a wide range of temperatures (2-30 • C; e.g. Tait and Schiel, 2013;Hancke et al, 2014;Ashton et al, 2017). The bacterial communities residing in marine sediments generally display a hyperbolic temperature-production relationship where GPP increases with T (∼ +32 % per 1 • C increase) until an optimal rate is reached roughly +2-3 • C above naturally observed seasonal maxima.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the ability to respond to "perturbing" cues, such as environmental changes, is a key feature to all organisms on Earth (Ashton et al, 2017;Kuntz and Eisen, 2014). The progression of a particular event needs to be coordinated to the timescale of development across the whole embryo.…”
Section: Introductionmentioning
confidence: 99%